Florida Solid and Hazardous Waste Regulation Handbook: Solid and Hazardous Waste Disposal - Michael T. Olexa; Aaron Leviten; Kelly Samek (EDIS, 2004)
This is EDIS document FE457, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, UF/IFAS, University of Florida, Gainesville, FL. Published December 2003.